Use of Project ECHO Telementoring Model in Continuing Medical Education for Pediatricians in Vietnam: Preliminary Results. (August 2021) - Nhung, Le Hong; Dien, Tran Minh; Lan, Nguyen Phuong; Thanh, Pham Quoc; Cuong, Pham Viet
The ECHO (Extension for Community Health Outcomes) model has been introduced and implemented in several hospitals and health programs in Vietnam since 2015. In 2018, Vietnam National Children's Hospital (VNCH) officially implemented the ECHO model to provide continuing medical education (CME) credits on pediatrics topics for medical staff in its satellite hospitals and health centers in the Northern region of Vietnam. This paper presents preliminary results of the ECHO program at VNCH. Methods included pre- and post-program assessments of pediatricians' clinical knowledge, self-efficacy, and professional satisfaction. The analysis compared the differences between pre/post scores descriptively. Knowledge of participants increased by 22.5% points on average. More than 90% of Project ECHO-Pediatrics participants experienced increased confidence. Overall, there was an improvement in participants' self-efficacy in the post-training compared to the pre-training (range 14.7%-22.6% difference from pre-training). All participants improved on their results in the clinical test immediately after the training and maintained it after 3 months. The study demonstrated the ability Project ECHO to improve healthcare worker knowledge and satisfaction.